"Something's Afoot" Post-Show at Mercedes Edwards Theater at Clark Intermediate School - Watkins, Howard::::::::: (1987)
Sarah Shacklett, Debbie Wassom, Diana Head, Katie Rea and Bob Williams; in back Ted Williams